2014
DOI: 10.1007/s00213-014-3641-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurochemical assessment of salvinorin A abuse potential in the rat

Abstract: Salvinorin A differs from other commonly abused compounds since although it affects accumbal dopamine transmission, yet it is unable, at least at the tested doses, to sustain stable intravenous self-administration behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Acute and chronic effects of salvinorin A on dopaminergic systems may also differ ( Gehrke et al, 2008 ), of possible relevance to repeated users of salvinorin A-containing products. Paradoxically, some studies have reported that relatively smaller salvinorin A doses cause a detectable enhancement of dopamine dialysate levels ( Braida et al, 2008 ; Serra et al, 2015 ). The differential mechanisms involved in this latter effect have not been fully elucidated.…”
Section: Salvinorin a Effects In Preclinical Assays For Neuropsychiatmentioning
confidence: 99%
“…Acute and chronic effects of salvinorin A on dopaminergic systems may also differ ( Gehrke et al, 2008 ), of possible relevance to repeated users of salvinorin A-containing products. Paradoxically, some studies have reported that relatively smaller salvinorin A doses cause a detectable enhancement of dopamine dialysate levels ( Braida et al, 2008 ; Serra et al, 2015 ). The differential mechanisms involved in this latter effect have not been fully elucidated.…”
Section: Salvinorin a Effects In Preclinical Assays For Neuropsychiatmentioning
confidence: 99%
“…An important consideration is the interaction of the endocannabinoid and its cannabinoid CB1 receptor with KOP in the pathophysiology of mood disorders and anxiety [52,53] . Upon with influences unlike those of other κ agonists [3] .…”
Section: Kop In Depression and Anxietymentioning
confidence: 99%
“…Preclinical findings include that, as with most other hallucinogens, lab animals failed to readily self- administer Salv A [ 88 ]. Indeed, results with animal models suggest that the drug reduces activity of DA in the BRS and even is aversive [ 88 ].…”
Section: The Special Case Of Salvinorin Amentioning
confidence: 99%